The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2478/fsmu-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Changes of monoterpenes in stem of Chinese white pine (Pinus armandi) saplings following treatment with Methyl Jasmonate

Abstract: The Chinese white pine beetle (Dendroctonus armandi Tsai and Li) is the causal organism for the colossal death of the Chinese white pine (Pinus armandi Fr). We investigated the change of monoterpenes in the stem pholem and xylem in P. armandi saplings at 4 days, 8 days, and 30 days after treatment using treatment (MeJa + Tween-20 and Tween-20 as control) and untreated. GC-MS analysis found that the total monoterpene concentrations in the pholem and xylem in MeJa-treated saplings increased significantly compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Plants treated with MeJA exhibited an increase in the amounts of terpenes such as α-pinene, β-pinene, limonene, β-phellandrene, camphene, calarene, myrcene and even (+)-3-carene. Terpene accumulation following MeJA treatment has been previously described to occur in Norway spruce ( Franceschi et al, 2002 ; Martin et al, 2002 ; Erbilgin et al, 2006 ; Zulak et al, 2009 ; Zhao et al, 2010 ), and also in other conifer species (e.g., Hudgins et al, 2003 ; Erbilgin and Colgan, 2012 ; Pham et al, 2014 ; Lundborg et al, 2019 ; Chen R. et al, 2020 ). In line with our findings, Zhao et al (2010) and Lundborg et al (2016b) found that α-pinene and limonene respond strongly to treatment with MeJA in Norway spruce.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Plants treated with MeJA exhibited an increase in the amounts of terpenes such as α-pinene, β-pinene, limonene, β-phellandrene, camphene, calarene, myrcene and even (+)-3-carene. Terpene accumulation following MeJA treatment has been previously described to occur in Norway spruce ( Franceschi et al, 2002 ; Martin et al, 2002 ; Erbilgin et al, 2006 ; Zulak et al, 2009 ; Zhao et al, 2010 ), and also in other conifer species (e.g., Hudgins et al, 2003 ; Erbilgin and Colgan, 2012 ; Pham et al, 2014 ; Lundborg et al, 2019 ; Chen R. et al, 2020 ). In line with our findings, Zhao et al (2010) and Lundborg et al (2016b) found that α-pinene and limonene respond strongly to treatment with MeJA in Norway spruce.…”
Section: Discussionmentioning
confidence: 92%
“…Samples of approx. 1.5 cm 2 in size were chopped into smaller pieces (following standard protocol as described in Persson et al, 1993;Axelsson et al, 2020), and each was immediately placed (using tweezers) in a 2-ml glass vial with solvent. Phloem samples were extracted in 0.5 mL n-hexane (VWR, Ref no.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…It also induces formation of traumatic resin ducts and polyphenolic parenchyma cells (Hudgins et al 2004). Partly because of their potential applications in pest control, physiological and chemical responses to MeJA have been widely studied in both conifer seedlings (Fäldt et al 2003; Gould et al 2008; Heijari et al 2005; Moreira et al 2009, 2012; Pham et al 2014; Zeneli et al 2006) and trees (Erbilgin et al 2006; Fäldt et al 2003; Schiebe et al 2012; Zhao et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…However, the origins and functions of myrtenol, myrtanol and myrtenal remain unclear. Myrtenol, myrtanol and myrtenal have been detected only in newly invaded female D. armandi , and have been detected in P. armandi in previous studies . To eliminate the effects of different test methods, the presence of myrtenol, myrtanol and myrtenal in healthy and infected P. armandi , and in both newly emerged and emerged D. armandi was investigated using a uniform approach.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The identification of host and bark beetle volatiles is usually performed using gas chromatographic and mass spectrometry (GC-MS) analyses. To investigate these compounds in relation to D. armandi, volatiles from the needles, resin and phloem of healthy and infected P. armandi [24][25][26][27][28] ; the air surrounding attacked and healthy P. armandi logs 5 ; and the hindgut extracts of female (mated and unmated) 4,5,29 and male 29 D. armandi and their frass 27,29 have been analysed by GC-MS in recent years, and some terpenes, sesquiterpenes and alkenols have been identified. However, because these studies used different test methods and had different emphases, the presence of some-micro volatiles has not been uniformly analysed.…”
Section: Introductionmentioning
confidence: 99%